THE EFFECTIVENESS OF PICTURE BOOKS ON STUDENTS’ NARRATIVE TEXT WRITING SKILLS - Cahyadi, Riyandi Agil; Darajat, Ageung; Sari, Dian Shinta (Program Studi Pendidikan Bahasa Inggris, 2025)
Abstract This study aimed to examine whether there was a difference in students’ narrative text writing performance before and after the implementation of Picture Books as a teaching medium, and to explore the extent of that difference among tenth-grade students of TKJ 3 at SMKN 1 Nanga Pinoh during the 2025/2026 academic year. The research employed a quantitative method using a pre-experimental one-group pre-test and post-test design. The results showed that the standard deviation of the pre-test was 5.26, slightly higher than the post-test, which was 5.25. A paired sample t-test revealed a statistically significant difference between the pre-test and post-test scores (t-obtained = 7.317; p < 0.05). Additionally, the effect size calculated using Cohen’s d was 1.29, indicating a strong magnitude of difference. While the findings suggest a potential association between the use of Picture Books and improved narrative writing performance, they should be interpreted with caution due to the absence of a control group. The results are indicative, not conclusive, regarding instructional effectiveness. Keyword: Picture Books, Writing Skills, Narrative Text,Pre-Experimental Research